Tradeoffs among delay, rate, and amount of reinforcement - Mazur, James E (Behavioural Processes, 2000)
In Experiment I, an adjusting-delay procedure was used to measure pigeons' choices between a single delayed reinforcer and a range of different variable-time schedules. Indifference points showed an inverse relation between rate of reinforcement and delay that was well described by a hyperbolic equation. An adjusting-amount procedure was used in Experiment 2, in which pigeons chose between an adjusting amount of food delivered after a 0.5-s delay and 3 s of food delivered after a range of different delays, and the effects of delay were similar to those found in Experiment 1. The results from both experiments indicated that, for pigeons, the strength of a reinforcer decreased rapidly with increasing delay. Estimates of a decay rate parameter in the hyperbolic equation were similar to those found in other studies with pigeons, but the rates of temporal discounting were three or four times faster than those found in studies with rats, suggesting a possible species difference. (C) 2000 Published by Elsevier Science B.V. All rights reserved.
64 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-033-972-981-013 tex.type: [object Object]
Keywords: Adjusting procedure; Amount of reinforcement; Delay; Discounting; Key peck; Pigeons; Rate of reinforcement; animal experiment; article; behavior; controlled study; dept.psy; dose time effect relation; nonhuman; pigeon; reinforcement; technique; variance